Utility of salivary biomarker for stress induced by dental treatment - Kiyoshi Ohura; Tadashige Nozaki; Mitsuko Shinohara; Kiyoshi Daito; Mie Sonomoto; Michiharu Daito (Elsevier, 2012)
To appropriately and smoothly perform dental treatment, the objective evaluation of patients' stress during treatment is important, for which effective means and methods to measure stress-related markers in simply and noninvasively collectable saliva have been investigated. In this review, saliva was collected from pediatric patients before and after treatment, and sIgA, α-amylase, and cortisol were measured to evaluate the stress of dental treatment on them. On analysis of the duration and content of treatment in dental records, the sIgA level showed a clearer response to stress compared to α-amylase and cortisol. Measurement of changes in the salivary sIgA level may be a useful, noninvasive stress evaluation method, and sIgA may serve as a stress marker.